2012
DOI: 10.1007/s00216-012-6071-y
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale profiling of diterpenoid glycosides from Stevia rebaudiana using ultrahigh performance liquid chromatography/tandem mass spectrometry

Abstract: The plant Stevia rebaudiana accumulates a suite of diterpenoid metabolites that are natural sweeteners finding increased use as sugar substitutes. To guide breeding of stevia plants that accumulate substances with desirable flavor in high yield, rapid and accurate methods are needed to profile these substances in plant populations. This report describes an 8-min ultrahigh performance liquid chromatography-tandem mass spectrometry method for separation and quantification of seven stevia glycosides including ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…9, B-D. Fragmentation of the oligogalactolipids resulted in expected peaks, including free fatty acids, lysolipids, and three forms in which both acyl tails were lost. In these forms, the headgroup remained attached to a version of the glycerol backbone, based on previous analyses of galactolipid fragmentation (83). Together with previous studies, these data confirm that the products are as suggested and that SFR2 is processive.…”
Section: Sfr2 Structural Modeling As a Framework For Understanding Susupporting
confidence: 87%
“…9, B-D. Fragmentation of the oligogalactolipids resulted in expected peaks, including free fatty acids, lysolipids, and three forms in which both acyl tails were lost. In these forms, the headgroup remained attached to a version of the glycerol backbone, based on previous analyses of galactolipid fragmentation (83). Together with previous studies, these data confirm that the products are as suggested and that SFR2 is processive.…”
Section: Sfr2 Structural Modeling As a Framework For Understanding Susupporting
confidence: 87%
“…Hence, steviolbioside was considered as an intermediate and not the rubusoside [31]. But isolation of rubusoside from Stevia has now been reported that suggests the possible involvement of this compound in steviol glycoside biosynthesis [33]. Additionally, rubusoside has been considered superior to stevioside because latter possessed a bitter after-taste [34].…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was transferred to a new 1.5-mL centrifuge tube. Extract supernatant was prepared for analysis by using a Millipore deep well filter plate and deep well 96-well receiving plate (Millipore Corporation, Billerica, MA) as previously described by Shafii et al (2012). Stevioside and rebaudiosides A, B, and C were quantified by ultra-high performance liquid chromatography-tandem mass spectrometry as previously described (Shafii et al, 2012) with the addition of rebaudioside D quantification with the following parameters: multiple reaction monitoring (MRM) transition m/z 1127 > 803, retention time 2.6 min, declustering potential -35 V, entrance potential -10 V, and collision potential -45 V. Morphological data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Extract supernatant was prepared for analysis by using a Millipore deep well filter plate and deep well 96-well receiving plate (Millipore Corporation, Billerica, MA) as previously described by Shafii et al (2012). Stevioside and rebaudiosides A, B, and C were quantified by ultra-high performance liquid chromatography-tandem mass spectrometry as previously described (Shafii et al, 2012) with the addition of rebaudioside D quantification with the following parameters: multiple reaction monitoring (MRM) transition m/z 1127 > 803, retention time 2.6 min, declustering potential -35 V, entrance potential -10 V, and collision potential -45 V. Morphological data collection. At the time of tissue collection for glycoside analysis, the number of nodes on the tallest branch (opposite and alternate nodes were each counted as one), canopy height (cm, from soil line to tallest point), and average leaf area (one leaf measured twice collected from the seventh node down from the apex of the tallest branch) were determined.…”
Section: Methodsmentioning
confidence: 99%